Interdisciplinaridade e Contextualização no Ensino de Ciências da Natureza e suas Tecnologias: o Estudo de Caso do Projeto “Ciência e Pandemia” - Santana, Ívina Langsdorff (2022)
The COVID19 pandemic affected society, the economy, human and work relationships and, consequently, the school. In-person classes have been suspended and, in their place, remote teaching was instituted. In this thesis, a case study was carried out on the pedagogical intervention project “Science and Pandemia”, which consisted of a series of interviews with health professionals and/or academics, in the live format on Instagram of a public school, integrating the subjects in the areas of Natural Sciences and Mathematics to explain scientific concepts and technologies used in the pandemic, during remote teaching. After the lives were performed, the content was transcribed on a website and an online activity form was launched to evaluate the interviews. The project, which took into account data on the accessibility and motivations of students with remote teaching, was able to increase their engagement with this teaching modality. As a product, the project provided quality, accessible and relevant digital content for science teaching, which was analyzed in this work in the light of Discursive Textual Analysis (DTA). In the case studied, the organization of the project in the pandemic context took place at the curricular, didactic and pedagogical levels of school interdisciplinarity described by Lenoir (1998) and corroborates the concept of school interdisciplinarity defended by Fazenda (1994; 2008; 2013ª; 2013b). Through the ATLAS.ti® software, version 9.0, it was possible to show graphically how the disciplines of Physics, Chemistry, Biology and Mathematics were related in the digital content. Using the Tetrahedron of Humanistic Teaching of Chemistry (TEHQ) by SJÖSTRÖM and TALANQUER (2014), it was possible to identify a contextualization of Chemistry at the applied and social levels in the analyzed content. In an emergent way and inspired by the TEHQ, the ATD was able to provide a theoretical basis for the development of the Tetrahedron of Humanistic Contextualization of Science Teaching, which serves to analyze the contextualization at the applied, sociohistorical and critical levels of any textual content.